Educational visit of Zhejiang Medical University delegates: A valuable summer experience / Muhammad Syazwan Mazlan and Associate Prof. Dr. Mahmathi Karuppannan - Mazlan, Muhammad Syazwan; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
On 2nd August 2023, the Faculty of Pharmacy, UiTM welcomed 17 students and 1 lecturer from the Faculty of Pharmaceutical Science, Zhejiang Medical University (ZMU). This visit was organised by the National Council of Professors (Majlis Profesor Negara) as part of ZMU's Summer Camp Programme in Malaysia, making it a significant academic and cross-cultural exchange event. The host, represented by the respected Deputy Dean(s) and lecturers as well as representatives from students' association SOPHYS and SMF, welcomed the delegation with a vibrant sharing session, that began with an insightful introduction to the faculty, including its rich history, academic outline, and diverse range of programs offered. The students from both institutions engaged in lively discussions, fostering a sense of closeness and a deeper understanding of their respective educational systems.